Potential seismic landslide hazard and engineering effect in the Ya’an-Linzhi section of the Sichuan-Tibet transportation corridor, China - Zhi-hua Yang; Chang-bao Guo; Rui-an Wu; Wei-wei Shao; Peng-fei Yu; Cai-hong Li (China Geology, 2023)
ABSTRACT: The Sichuan-Tibet transportation corridor is located at the eastern margin of the Qinghai-Tibet Plateau, where the complex topography and geological conditions, developed geo-hazards have severely restricted the planning and construction of major projects. For the long-term prevention and early control of regional seismic landslides, based on analyzing seismic landslide characteristics, the Newmark model was used to carry out the potential seismic landslide hazard assessment with a 50-year beyond probability 10%. The results show that the high seismic landslide hazard is mainly distributed along large active tectonic belts and deep-cut river canyons, and are significantly affected by the active tectonics. The low seismic landslide hazard is mainly distributed in the flat terrain such as the Quaternary basins, broad river valleys, and plateau planation planes. The major east-west linear projects mainly pass through five areas with high seismic landslide hazard: Luding-Kangding section, Yajiang-Xinlong (Yalong river) section, Batang-Baiyu (Jinsha river) section, Basu (Nujiang river) section, and Bomi-Linzhi (eastern Himalaya syntaxis) section. The seismic action of the Bomi-Linzhi section can also induce high-risk geo-hazard chains such as the high-level glacial lake breaks and glacial debris flows. The early prevention of seismic landslides should be strengthened in the areas with high seismic landslide hazard.©2023 China Geology Editorial Office.